PENGARUH KINERJA KEUANGAN PADA ALOKASI BELANJA MODAL DAN PERTUMBUHAN EKONOMI PEMERINTAH KABUPATEN/KOTA SE-PROVINSI BALI TAHUN 2006 S.D. 2013 - Arsa, I Ketut; Djinar Setiawina, Nyoman (Buletin Studi Ekonomi, 2016)
The Impact of the Financial Performance Component on Capital Expenditures and Economic Growth. This study was aimed to examine the directly influence of the financial performance component on the capital expenditure of local government, examine the directly influence of the allocation of capital expenditure on economic growth and examine the indirectly influence of the financial performance on economic growth through capital expenditure of district/city in The Province of Bali. Data, analyzed using path analysis with Eviews program, were based on secondary data (a panel data that is a combination of cross section data with time series data). The results showed that the degree of  decentralization and effectivity of local revenue (PAD) had positive effect on capital expenditure, while the financial dependence had negative effect on capital expenditures. Capital expenditures had positive effect on economic growth. Three of the five indicators financial performance of local governments, such as the level of decentralization, financial dependence, and the effectiveness of local revenue (PAD),had indirectly effect on economic growth in the District/City throught allocation of capital expenditures in The Province of Bali.   Keywords: capital expenditures, economic growth, financial performance
Keywords: capital expenditures, economic growth, financial performance